Is Green Growth Good for the Poor? - Dercon Stefan (World Bank, Washington, DC, 2014)
The developing world is experiencing substantial environmental change, and climate change is likely to accelerate these processes in the coming decades. Due to their initial poverty and their relatively high dependence on environmental capital for their livelihoods, the poor are likely to suffer most due to their low resources for mitigation and investment in adaptation. Economic growth is essential for any large-scale poverty reduction. Green growth, a growth process that is sensitive to environmental and climate change concerns, can be particularly helpful in this respect. We focus on the possible trade-offs between the greening of growth and poverty reduction, and we highlight the sectoral and spatial processes behind effective poverty reduction. High labor intensity, declining shares of agriculture in GDP and employment, migration, and urbanization are essential features of poverty-reducing growth. We contrast some common and stylized green-sensitive growth ideas related to agriculture, trade, technology, infrastructure, and urban development with the requirements of poverty-sensitive growth. We find that these ideas may cause a slowdown in the effectiveness of growth to reduce poverty. The main lesson is that trade-offs are bound to exist; they increase the social costs of green growth and should be explicitly addressed. If they are not addressed, green growth may not be good for the poor, and the poor should not be asked to pay the price for sustaining growth while greening the planet.